Perancangan Platform E-Commerce Berbasis OpenCart untuk Promosi Produk Fashion dan Makanan UMKM di Kec. Baso - Putri, Fadhila; Annas, Firdaus; Salshavira, Najwabilla (JOVISHE : Journal of Visionary Sharia Economy, 2023)
The aim of this article is to design an online platform based on OpenCart that can be effectively used to promote fashion and food products for umkm in Baso District. With this platform, it is hoped that umkm can reach more customers and increase their sales. Apart from that, this aim also includes helping to improve the economy in the area, so that superior products from these umkm can be widely known, both within and outside the area. So far, promotions carried out by umkm are still carried out in traditional ways and are not widely known by the public, and market competition has also reduced the income of umkm owners. In fact, current technological advances have encouraged these products to become widely known in the global market. This research uses the Research and Development (R&D) model with the Define, Design, Develop, Decemination development model. This research found that the use of an online platform in the form of Opencart can increase the availability of umkm products in the global market to a wider extent, as well as simplify the transaction process between sellers and buyers. The implications of this research show the importance of using digital technology for umkm to increase competitiveness and local economic growth, as well as providing recommendations for related parties to support the implementation of online platforms among the community.